2010
DOI: 10.1186/1471-2164-11-690
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation in the myo1Δ mutant of Saccharomyces cerevisiae

Abstract: BackgroundSaccharomyces cerevisiae myosin type II-deficient (myo1Δ) strains remain viable and divide, despite the absence of a cytokinetic ring, by activation of the PKC1-dependent cell wall integrity pathway (CWIP). Since the myo1Δ transcriptional fingerprint is a subset of the CWIP fingerprint, the myo1Δ strain may provide a simplified paradigm for cell wall stress survival.ResultsTo explore the post-transcriptional regulation of the myo1Δ stress response, 1,301 differentially regulated ribosome-bound mRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(97 reference statements)
1
4
0
Order By: Relevance
“…Likewise, the accumulation of eIF2α-P in the wsc1 Δ mutant confirmed that TORC1 activity was down regulated in this mutant (Figure 7 , top panel, lane 3). Control extracts from the wt and myo1Δ strains were consistent with previously reported results [ 17 ]. Total eIF2α confirmed that the proposed changes in eIF2α-P were due to phosphorylation rather than a change in steady state levels of eIF2α (Figure 7 , middle panel).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Likewise, the accumulation of eIF2α-P in the wsc1 Δ mutant confirmed that TORC1 activity was down regulated in this mutant (Figure 7 , top panel, lane 3). Control extracts from the wt and myo1Δ strains were consistent with previously reported results [ 17 ]. Total eIF2α confirmed that the proposed changes in eIF2α-P were due to phosphorylation rather than a change in steady state levels of eIF2α (Figure 7 , middle panel).…”
Section: Resultssupporting
confidence: 92%
“…We then tested eIF2α phosphorylation levels as an additional readout of TORC1 status [ 63 ]. Previous studies showed that TORC1 down regulation in myo1Δ was evidenced by a large (2 fold) accumulation of phosphorylated eIF2α (eIF2α-P) produced by a TOR-dependent activation of Gcn2p protein kinase (Figure 7 , top panel) [ 17 ]. The myo1Δwsc1 Δ mutant combination that restored wild type electrophoretic mobility to Npr1p (Figure 6 A) also restored eIF2α-P to its active unphosphorylated state, eIF2α (Figure 7 , top panel, lane 4), thereby confirming that TORC1 was being reactivated in this mutant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larsson et al Beretta 2008;Ramirez-Valle et al 2008;Ceppi et al 2009;Dhamija et al 2010;Rivera-Ruiz et al 2010;Di Florio et al 2011). Commonly, fractions with two or more associated ribosomes are pooled, limiting the analysis of regulation to a shift from less than two to two or more associated ribosomes (i.e., "on -off " regulation), whereas other shifts (e.g., from three to nine associated ribosomes, i.e., "relative" regulation) are missed.…”
Section: Genome-wide Analysis Of Translational Activitymentioning
confidence: 99%
“…In addition to chemical or genetic perturbation of the cell membrane, the CWI pathway is stimulated by a wide variety of other stresses including nutrient starvation, hypo-osmotic shock, heat shock, and environmental conditions that perturb cell integrity functions ( Kamada et al 1995 ; Fuchs and Mylonakis 2009 ). Readouts of the CWI pathway include the enhanced transcription of genes encoding stress proteins and cell wall components, altered translational regulation, and the modulation of growth processes ( Kamada et al 1995 ; Gray et al 1997 ; de Nobel et al 2000 ; Zu et al 2001 ; Rodríguez-Quiñones et al 2008 ; Rodríguez-Quiñones and Rodríguez-Medina 2009 ; Rivera-Ruiz et al 2010 ; Rodicio and Heinisch 2010 ; Pagán-Mercado et al 2012 ; Yurko et al 2017 ; Leskoske et al 2018 ). The CWI pathway also controls genes involved in other biological processes such as regulation of cytoskeleton polarization ( de Nobel et al 2000 ), the activity of cell wall biosynthetic enzymes ( Levin 2011 ), polarized cell growth ( Zarzov et al 1996 ), and the control of target of rapamycin complex 1 (TORC1) ( Petkova et al 2010 ) and TORC2 complexes ( Leskoske et al 2018 ).…”
mentioning
confidence: 99%